ANALYSIS OF TEACHER PERFORMANCE ASSESSMENT USING THE 360 DEGREE FEEDBACK METHOD IN VOCATIONAL HIGH SCHOOLS - Elida Tuti Siregar; Nita Syahputri; Nurhayati Nurhayati; Erwin Ginting (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Teacher performance assessments in vocational education units need to be designed objectively, comprehensively, and involve various sources of assessors so that the portrait of teacher work quality can be mapped more reliably. This study aims to analyze the application of the 360-degree feedback method in the performance assessment process of productive TKJ and RPL teachers at SMK PAB 8 Sampali. The study used a mixed method approach with data collection through Likert-scale questionnaires, interviews, and learning document reviews. The research subjects were 20 productive teachers. Data analysis was carried out by converting quantitative scores and strengthening qualitative narratives through source triangulation. The results showed that the application of 360-degree feedback provided a more balanced assessment picture through the involvement of the principal, colleagues, students, and teacher self-evaluation. These findings reinforce the urgency of using multi-source-based assessments to improve the quality of the learning process in competency-based vocational schools